(untitled) (Journal of Fiber Bioengineering and Informatics, 2014)
Thermoregulatory manikin can simulate complex physiological human behaviors such as sweating, shivering and vasomotion which the human body uses in order to adapt to temperature changes in the environment. Thus, it serves as a better simulation for human responses in the thermal environment than traditional ones. This paper first discusses the limitations of traditional manikins then followed by a summary of suitable thermal physiological models which have been implemented on manikins. A review of the development and application of thermoregulatory manikin is made by comparing research achievements of different research institutes. Currently, the thermal manikin system controlled by thermal physiological model has yet to be matured, which needs further validation before laboratory applications.